Detection of the vortices signs in the scalar fields - Galushko, Yuriy; Mokhun, Igor (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The technique for determining the vortex sign in the scalar fields (including the statistical ones) under conditions when the use of the regular reference beam is impossible is described. The elaborated approach is based on the shift-interferometry technique. The conditions of the optimal vortices identification are formulated. The results of the computer simulation and experimental confirmation are presented.
Optica Applicata, Vol. 38, 2008, nr 4, s. 705-713
Keywords: optyka; vortex; shift-interferometry; interference forklets; topological charge